Prosecutor's Demand In Delimination Form Of Children's Independence As A Form Of Legal Protection - Suhardjono Suhardjono; Siti Ummu Adillah (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to find out and analyze whether the prosecutor's demands containing the deprivation of liberty against children have been appropriately applied in the context of legal protection to children, especially in sexual crimes committed by children against children. The approach method used in this research is empirical juridical with the specification in this research is descriptive analysis, which describes the applicable laws and regulations associated with legal theories in the practice of implementing positive law concerning problems. The results obtained are that the prosecutor's demands in the form of formal deprivation of liberty and seen from the aspect of legal objectives are in accordance with Act No. 11 of 2012 concerning the Juvenile Criminal Justice System, besides that from a sociological and philosophical point of view it is felt to be comparable to trauma and suffering a lifetime experienced by the victim's child in facing his future.